A Qualitative Exploration of the Absence of Sport Psychologists in Sport Clubs: The Coaches' Perspective - Mohammed, Warhel (Humanities Journal of University of Zakho, 2022)
Objectives The purpose of this qualitative study was to confirm the effects of the absence of sport psychologists in sport clubs from the perspective of the coaches. Furthermore, to investigate the effects of this absence on athlete performance, as well as the reasons for eliminating this specialty at sport clubs. Methods The researcher used a descriptive approach with an inductive method to identify the participants' visions and interpretations. Thematic Analysis, a qualitative data analysis method in descriptive research (Braun & Clarke, 2006), were used to analyze data in this study. NVivo coding, a computer software package for analyzing qualitative data, was used by the researcher to analyze all of the interview texts.. Results Once the data collection is complete, all interviews were thematically identified and categorized into four themes. The following topics were identified as themes: 1) The professional system at sports clubs, 2) The economic component, 3) The prevalent social culture, and 4) The lack of application of governance principles in sports federations and clubs. These were the most prominent themes that emerged from coaches' visions and interpretations based on their experiences in sports clubs. Conclusions Due to a lack of psychological preparation in pre and post-sport competitions, there is a gap in the training process. This results in a decline in both physical and psychological aspects in athletes, as well as the possibility of psychological distress. A lack of psychological preparation may also be an impediment for sports clubs.